Nexus Between Corporate Governance, Debt Structure, Earnings Management in Family Firms: Perspective an Agency Theory - Agoestina Mappadang; Roza Fitriawati; Melan Sinaga (AFRE (Accounting and Financial Review), 2024)
This study aims to analyze the impact of family ownership on earnings ma-nagement,Â  explain the impact of family ownership on internal governance me-chanisms, examine the impact of internal governance mechanisms on earnings management, examine the impact of debt structure on earnings management. This study confirms the Agency Theory in the family ownership chart setting, tested through the use of 6 hypotheses. The research sample uses a purposive sampling method in the Consumer Non-Cyclicals sector, which has been listed on the Indonesia Stock Exchange from 2019 to 2022. Data analysis will be carried out with path analysis. The results of this research have implications for the characteristics of ownership of public companies in Indonesia which are unique. Apart from being concentrated, the majority of shares are owned by the family. Agency problems in this condition shift no longer between the family and the manager because generally the manager is a party who has a kinship relationship, but between families with non-family owners and third parties. The agency problem found in this research is between the family and debt-holders and potential stockholders. Agency problems between families and managers and minority owners are not proven in this research because ma-nagers are generally also parties who have kinship relationships so managers have aligned interests with the family. The small minority shareholding causes the family to ignore this agency conflict.DOI: https://doi.org/10.26905/afr.v7i2.12952Â